Author Correction: Sarcolab pilot study into skeletal muscle's adaptation to longterm spaceflight. (December 2018) - Rittweger, Jörn; Albracht, Kirsten; Flück, Martin; Ruoss, Severin; Brocca, Lorenza; Longa, Emanuela; Moriggi, Manuela; Seynnes, Olivier; Giulio, Irene; Tenori, Leonardo; Vignoli, Alessia; Capri, Miriam; et al.
The original version of this Article contained an error in the spelling of the author Claudio Franceschi, which was incorrectly given as Claudio Francheschi. This has now been corrected in both the PDF and HTML versions of the Article.